Socio-Demographic and Clinical Profile of COVID-19 in Children (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2024)
Background: Coronavirus disease 2019 (COVID-19) caused by SARS-CoV-2 is a global pandemic. Infection by COVID-19 in children is not so common but gradually the numbers of children affected with COVID-19 are increasing day by day. Covid-19 has spread around Bangladesh and children are also being infected with comparatively fewer symptoms and lower case-fatality rates. To describe the epidemiological and clinical characteristics of hospitalized children with COVID-19. Materials and methods: This cross sectional observational study was conducted among 154 COVID-19 children who were admitted in COVID-19 dedicated Chattagram Maa Shishu O General Hospital, Chattagram from 15 April 2020 to 21 August 2022. Their signs, symptoms, sex, age distribution, laboratory results and familial contact were analyzed. Results: Among 154 children total RT-PCR positive cases were 82 (52%) and suspected cases were 72 (47%). Among positive casesmale-female ratio was 1.78:1. Most of the children (64%) were in school going age (6-18 years).70% children were from urban area and 30% from rural area. Most of the children (78%) came from middle and upper middle socioeconomic group and 22% from lower socioeconomic group. About 74% children were affected from family member.Main symptoms of the children were cough (72%), and fever (62%), fever with cough (56%) and diarrhoea (26%). About 58% of the children had additional symptoms including sore throat, nasal congestion, fatigue, headache, body ache, vomiting, abdominal pain, 32 patient came with shortness of breath. 7 patients had comorbidities. Among those 1 with CKD, 1 CP, 2 TB and 3 patients had asthma. Total 6 patients were died, 2 patients from positive cases and 4 patients from suspected cases. Among those 1 was CP child. About 14% patients showed lymphopenia, 14% showed leucopenia, 38% patient had neutropenia. C-Reactive Protein (CRP) and serum ferritin were high in only 52% and 38% cases respectively. There were 30% patients who had normal Chest X-Ray and 12% had bilateral consolidation and 58% had patchy opacities. Conclusion: The clinical manifestations in children are variable. However, fever and cough have mostly been profiled. Though the severe condition is rarely reported in children compared with adults, life-threatening complications, and death associated with COVID-19 disease have been documented. But it is evident that they may play a role in transmission of disease.Chatt Maa Shi Hosp Med Coll J; Vol.22 (2); July 2023; Page 14-17